Comportamiento de híbridos de maíz frente al achaparramiento del maíz causado por Spiroplasma kunkelii en la región del noroeste argentino (NOA) – Campaña 2023-2024 = Response of maize hybrids to corn stunt disease caused by Spiroplasma kunkelii in the Argentine Northwest (NOA) – 2023-2024 growing season - Araujo, Leonardo; Druetta, Marcelo Alberto; Torrico Ramallo, Ada Karina; Gimenez, Maria De La Paz; Barontini, Javier Miguel (Facultad de Ciencias Agropecuarias, Universidad Nacional de Córdoba, 2025)
Corn stunt disease (CS) is caused by Spiroplasma kunkelii, Maize rayado fino virus (MRFV), Maize bushy stunt phytoplasma (MBSP) and Maize striate mosaic virus (MSMV) and transmitted by Dalbulus maidis. During 2023–2024, it severely affected corn production in Argentina, with losses of 20 %. Fourteen commercial maize hybrids were evaluated in locations across the Argentine Northwest (NOA) to determine their performance, incidence and severity in response to the disease. The results showed incidence values ranging from 8 % to 100 %, with severity varying among the hybrids. The performance was above average in SYN505VIP3, DK7210PRO4, DK7220PRO4, P2297PWUE, and PAN5175PWU. SYN505VIP3 showed mild symptoms and low severity. Although DK7210PRO4, DK7220PRO4, P2297PWUE, and PAN5175PWU had more severe symptoms, their performance was not significantly impacted, though there was some variability in P2297PWUE and PAN5175PWU. In contrast, BRV8380PWE, DK7272VT3P, BRV8421PWUE, ZEFIRPWU, and NEXT22.6PWUE, with similar severity, had below-average performance, with particularly high severity in NEXT22.6PWUE and ZEFIRPWU. Regression analysis revealed that the severity index explains 72 % of the variability in performance, with each additional unit of severity associated with an average reduction of 15.96 kg/ha in yield. This underscores the importance of selecting suitable hybrids to mitigate the impact of CS.